Auditoría tributaria y su relación con la información financiera de la empresa estación de servicios Salvaggio S.A, cantón Quevedo, año 2014 - Merizalde Zamora, Fernanda Carolina (2015)
Research work conducted at the Service Station Salvaggio SA, is located in Canton Road Valencia Quevedo 1 ½ km, had as its main objective the execution of a Tax Audit to verify its relationship with the financial information. For the execution of this work was necessary to use an appropriate methodology based on the objectives, a questionnaire internal control consented evaluating control activities where different findings were identified giving as a result a confidence level of 75% considered it was applied Moderate high and a risk level of 25% considered under Moderate, substantive testing was developed and succeeded in identifying the performance of each of the obligations of the company, letting us know that the station serves, partly complies with the tax obligations before the Service Internal Revenue finally the analysis and comparison of financial information with the information declared by the taxpayer where it was observed that the accounting information is reasonably declared referring to these items was made, also allowed us to measure the profitability of the company where We appreciate that during the fiscal period audited losses found due to poor existing accounting management, which determined that the company was exceeded in the areas of costs and expenses compared to income perceived. All this methodology was used to issue the audit report where the results found during the process, in which we reported the results of recálculo audit found irregularities generated by a value of $ 3,600.00 payable communicates. As mentioned above it is recommended to Salvaggio SA Service Station, take regulatory measures in order to obtain the correct operation of internal control that allows you to plan each of the activities undertaken within the company, in order to control these anomalies.